Using the Elaboration Likelihood Model to Explain Performance Appraisal Inaccuracies - Larsen, Don A. (Journal of Management Policy and Practice, 2019)
Performance appraisal inaccuracy has received research attention partly due to actual job performance explaining a small portion of rating variance. This paper uses the Elaboration Likelihood Model (ELM) to explain how and when factors unrelated to job performance will influence the performance evaluation process due to a rater’s lack of ability or motivation. Potential variables affecting rater motivation and ability to accurately assess employee performance are explained via the ELM, and several factors shown in previous research to affect rater accuracy are explained via the ELM framework. Suggestions for future research examining performance appraisal accuracy via the ELM are provided.